Studying the Cooling Rate Effect Within Different Temperature Range on Platelet Damage Extent - Gurina, T. M.; Knysh, O. V.; Kompaniets, A. M. (Problems of Cryobiology and Cryomedicine, 2007)
There was investigated the cooling rate effect within temperature range of cryobiological system crystallisation and low temperature eutectic stratification of cryoprotectant solution on human blood platelet damage extent, determined by cytosol enzyme activity in extracellular medium after cryopreservation. Passing through the mentioned temperature range with the certain controlled rate was shown to significantly reduce the blood platelet damage extent.